Learning Innovation through the Development of Interactive Multimedia Based on Local Wisdom for Sociology Learning in the Digital Era - Noeryanti, Ari Tri; Rejekiningsih, Triana; Sudiyanto (Universitas Pendidikan Ganesha, 2023)
The need for innovative digital learning media makes learning activities less attractive to students. Even though technological developments have paved the way for various innovations in aspects of learning, such as interactive multimedia, this study aims to develop appropriate interactive multimedia for sociology learning. This research is included in research and development (RnD) with a 4D model. The data collection method uses a non-test: a needs analysis questionnaire and a media feasibility questionnaire. The data collection instrument used a questionnaire. Data analysis techniques use descriptive and percentage techniques. The study results show that students have a good view and agree with the presence of interactive multimedia. It is in line with the finding that during the learning process, teachers have used ICT. The results of the average evaluation of multimedia products by material experts obtained a score of 83% which was included in the very feasible category, by media experts obtained an average of 86% which was included in the very feasible category. Interactive media is included in the appropriate category for sociology learning media. It is hoped that the results of this research can become an innovation in ICT-based learning processes.